2019
DOI: 10.1088/1555-6611/ab4bdc
|View full text |Cite
|
Sign up to set email alerts
|

Experimental reconstruction of spatial Schmidt modes for a wide-field SU(1,1) interferometer

Abstract: We study the spatial mode content at the output of a wide-field SU(1, 1) interferometer, i.e. a nonlinear interferometer comprising two coherently-pumped spatiallymultimode optical parametric amplifiers placed in sequence with a focusing element in between. This device is expected to provide a phase sensitivity below the shot-noise limit for multiple modes over a broad angular range. To reconstruct the spatial modes and their weights, we implement a simple method based on the acquisition of only intensity dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…(1) R,A can be also arranged in 2-dimensional arrays and analyzed (see, for example, [24]). Similarly, in some cases the factorization takes place for x and y Cartesian coordinates [17].…”
Section: Full Dimensionality Of the Correlation Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) R,A can be also arranged in 2-dimensional arrays and analyzed (see, for example, [24]). Similarly, in some cases the factorization takes place for x and y Cartesian coordinates [17].…”
Section: Full Dimensionality Of the Correlation Functionsmentioning
confidence: 99%
“…By using a central wavelength detuned from the degenerate one (709.3 nm), we remove the idler modes matching with the signal. In this way, we select only one of the twin beams and the typical cross-correlation of intensity fluctuations between signal and idler modes disappears [24,31]. Since the detuning from degenerate wavelength is small, the reconstructed modes do not differ from the eigenmodes of the degenerate PDC.…”
Section: A High-gain Pdcmentioning
confidence: 99%
“…An excellent candidate for the role of photon source in various linear and nonlinear interferometric schemes is the parametric down-conversion (PDC), which is one of the most commonly exploited nonlinear processes for the creation of squeezed and entangled photons [14][15][16]. Pho-tons emitted via PDC, typically called signal and idler photons, are generated in broadband spatial and spectral modes, whose role in interferometry has already been proved both theoretically and experimentally [17][18][19][20][21][22][23]. As an example, it has been observed that the possibility of controlling the number of spectral modes, and therefore the amount of spectral/ temporal correlations between signal and idler photons, can determine the behaviour of the quantum interference pattern in the four-photon Hong-Ou-Mandel scenarios [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PDC sources generate photon pairs with finite spectral and spatial bandwidths and generally in more than a single mode. Therefore, the complete description of SU(1,1) interferometers should account for the presence of such spatial [29,30,31] and spectral modes [32,33,34] in order to correctly engineer the system [35] and accordingly maximize the phase sensitivity [36].…”
Section: Introductionmentioning
confidence: 99%